1997
DOI: 10.1159/000203546
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis and Secondary Necrosis of Lymphocytes in Culture

Abstract: It has been reported that cultured peripheral B lymphocytes of chronic lymphocytic leukemia (B-CLL) patients show a high degree of apoptosis (programmed cell death). Till now, no data exist about the occurrence of in vitro apoptosis of normal B and T cells. We measured the amount of apoptosis and secondary necrosis (type 2 necrosis) in B-CLL lymphocytes and in normal peripheral B and T lymphocytes in culture. Observations were made on B-CLL lymphocytes and on normal B and T cells purified by immunomagnetic cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0
1

Year Published

2000
2000
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(34 citation statements)
references
References 11 publications
3
30
0
1
Order By: Relevance
“…Ultrastructurally, the cytoplasm was electron-lucent and was highly edematous, the cytoplasmic organelles had dissolved, and only the plasma membranes and mitochondria remained intact. Therefore, we have tentatively concluded that these types of cell death are morphologically analogous to "necrosis", even if the initial characteristics resemble "apoptosis", and consequently, this cell death without mitochondrial lysis is envisaged as "secondary necrosis" [17,23,38].…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Ultrastructurally, the cytoplasm was electron-lucent and was highly edematous, the cytoplasmic organelles had dissolved, and only the plasma membranes and mitochondria remained intact. Therefore, we have tentatively concluded that these types of cell death are morphologically analogous to "necrosis", even if the initial characteristics resemble "apoptosis", and consequently, this cell death without mitochondrial lysis is envisaged as "secondary necrosis" [17,23,38].…”
Section: Discussionmentioning
confidence: 89%
“…Hong et al [17] and Kroemer et al [23] proposed that it is the entity of cell death which primarily becomes apoptotic and then induces necrosis, and they refer to this process as "secondary necrosis" in order to distinguish it from classical types of the necrosis. Vermes et al [38] proposed the term "putrosis" to designate the same post-apoptotic status. We were able to detect three types of TUNEL-positive cells; 1) TUNEL-positive cells with pycnotic nuclei but without cytoplasmic lysis, similar to the classical type of apoptotic cell, 2) TUNEL-positive cells with blebbed peculiar nuclei located in and between the acinar cells, which resembled the "degenerating apoptotic bodies", and 3) TUNEL-positive cells with completely lysed cytoplasm.…”
Section: Discussionmentioning
confidence: 99%
“…During the late phases of apoptosis, membrane integrity cannot be maintained, resulting in leakage of intracellular antigens (39)(40)(41). In this way, potential autoantigens may become accessible to the immune system.…”
Section: Discussionmentioning
confidence: 99%
“…Apoptosis was assessed by dual-colour immunofluorescent flow cytometry as described previously (Vermes et al, 1997;Pepper et al, 2003).…”
Section: Measurement Of In Vitro Apoptosismentioning
confidence: 99%